Effect of a parenting intervention on decreasing adolescents' behavioral problems via reduction in attachment insecurity: A longitudinal, multicenter, randomized controlled trial. (2nd August 2021) - Barone, Lavinia; Carone, Nicola; Costantino, Antonella; Genschow, Jennifer; Merelli, Sara; Milone, Annarita; Polidori, Lisa; Ruglioni, Laura; Moretti, Marlene M.
ABSTRACT: Introduction: Secure attachment in adolescence, related to caregiving quality, is a robust predictor of positive behavioral adjustment in early adulthood and beyond. Nevertheless, few attempts have been made to develop treatments to promote parent–adolescent attachment security. Methods: Using a longitudinal, multicenter, randomized controlled trial design, two questionnaire‐based studies were run in Italy (Study 1: n = 100 mothers of adolescents, 60% boys, M age = 14.89, SD = 1.58; Study 2: n = 40 mothers and 40 adolescents, 60% boys, M age = 14.90, SD = 1.91) to test the effectiveness of an attachment‐based parenting intervention (i.e., Connect) in reducing adolescents' behavioral problems and attachment insecurity 2 weeks post‐intervention (t2) and at a 4‐month follow‐up (t3). It was further investigated whether a decrease in avoidant and anxious attachment at t2 would account for changes in externalizing and internalizing problems, respectively, at t3. All adolescents belonged to two‐parent intact families. Results: Mothers who completed Connect reported significantly fewer adolescent behavioral problems and lower adolescent attachment insecurity, compared to mothers in the waitlist group, at both t2 and t3 (Study 1). These findings were confirmed in a second subsample (Study 2), considering both mothers' and adolescents' reports. Controlling for pre‐intervention behavioral problems, reductions in internalizing and externalizing problems were observed in both studies at t3 via a decrease in anxious and avoidant attachment, respectively, at t2. Conclusions: The findings point to the malleability of attachment security in adolescence and highlight the importance of targeting parenting quality to promote adolescent behavioral adjustment.